Enkephalin analogues with N-phenyl-N-(piperidin-2-ylmethyl)propionamide derivatives: Synthesis and biological evaluations. Issue 1 (1st January 2016) - Deekonda, Srinivas; Cole, Jacob; Sunna, Sydney; Rankin, David; Largent-Milnes, Tally M.; Davis, Peg; BassiriRad, Neemah M.; Lai, Josephine; Vanderah, Todd W.; Porecca, Frank; Hruby, Victor J.
Graphical abstract: Abstract: N -Phenyl- N -(piperidin-2-ylmethyl)propionamide based bivalent ligands are unexplored for the design of opioid based ligands. Two series of hybrid molecules bearing N -phenyl- N -(piperidin-2-ylmethyl)propionamide derived small molecules conjugated with an enkephalin analogues with and without a linker (β-alanine) were designed and synthesized. Both bivalent ligand series exhibited remarkable binding affinities from nanomolar to subnanomolar range at both μ and δ opioid receptors and displayed potent agonist activities as well. The replacement of Tyr with Dmt and introduction of a linker between the small molecule and enkephalin analogue resulted in highly potent ligands. Both series of ligands showed excellent binding affinities at both μ (0.6–0.9 nM) and δ (0.2–1.2 nM) opioid receptors respectively. Similarly, these bivalent ligands exhibited potent agonist activities in both MVD and GPI assays. Ligand17 was evaluated for in vivo antinociceptive activity in non-injured rats following spinal administration. Ligand17 was not significantly effective in alleviating acute pain. The most likely explanations for this low intrinsic efficacy in vivo despite high in vitro binding affinity, moderate in vitro activity are (i) low potency suggesting that higher doses are needed; (ii) differences in experimental design (i.e. non-neuronal, high receptor density for in vitro preparations versus CNS site of action in vitro); (iii) pharmacodynamics (i.e. engaging signalling pathways); (iv) pharmacokinetics (i.e. metabolic stability). In summary, our data suggest that further optimisation of this compound17 is required to enhance intrinsic antinociceptive efficacy.